Simultaneous Esterification and Transesterification of Neem Seed Oil Using Ferric Sulphate Doped With Poultry Droppings as a Bifunctional Catalyst - Akhabue, Christopher Ehiaguina; Ukponahiusi, Uwadiae Jonathan; Osa-Benedict, Evidence Osayi; Otoikhian, Shegun Kevin; Inetianbor, Oseghale Cyril; Oyedoh, Eghe Amenze (Frontiers in Energy Research, 2022)
The use of organic waste materials conjugated with inorganic sources as a bifunctional catalyst for one-step biodiesel production is currently under-utilized. In this study, a bifunctional catalyst for biodiesel production was developed from poultry droppings doped with ferric sulphate (FSPD). Its catalytic activity was investigated in simultaneous esterification and transesterification of neem seed oil (NSO) using methanol. Response Surface Methodology was employed in modelling and optimizing the reaction conditions. The characterization of the catalyst was done using Scanning Electron Microscopy equipped with Energy-Dispersive X-ray Spectroscopy, Fourier Transform Infrared Spectroscopy and X-ray Diffractometer. Fe (46.08 wt.%), S (22.31 wt.%) and Ca (11.82 wt. %) were the major elements present in the FSPD and the other results revealed that it is bifunctionally active. A biodiesel yield of 97.21 % and acid value (AV) of 0.5 mg KOH/g were obtained at the optimum conditions of 21:1 methanol/oil ratio, 5 wt.%, catalyst loading and reaction temperature of 65 oC after 180 min. The biodiesel produced using FSPD catalyst meets both the ASTM D6751 and the EN 14214 biodiesel standards. Reusability investigation of the FSPD showed remarkable stability up to the third reuse cycle with a slight decrease in biodiesel yield and a corresponding increase in acid value from 97.21 to 90.05 % and 0.5 to 0.81 mg KOH/g respectively. The utilization of FSPD as a bifunctional catalyst is significant for improving the biodiesel output of high FFA oil and overall biodiesel production time.